Low temperature gamma sterilization of a bioresorbable polymer, PLGA. (February 2018) - Davison, Lisa; Themistou, Efrosyni; Buchanan, Fraser; Cunningham, Eoin
Abstract: Medical devices destined for insertion into the body must be sterilised before implantation to prevent infection or other complications. Emerging biomaterials, for example bioresorbable polymers, can experience changes in their properties due to standard industrial sterilization processes. Gamma irradiation is one of the most reliable, large scale sterilization methods, however it can induce chain scission, cross-linking or oxidation reactions in polymers. sterilization at low temperature or in an inert atmosphere has been reported to reduce the negative effects of gamma irradiation. The aim of this study was to investigate the impact of low temperature sterilization (at −80 °C) when compared to sterilization at ambient temperature (25 °C) both in inert atmospheric conditions of nitrogen gas, on poly(lactide co-glycolide) (PLGA). PLGA was irradiated at −80 and 25 °C at 40 kGy in a nitrogen atmosphere. Samples were characterised using differential scanning calorimetry (DSC), tensile test, Fourier transform infrared (FTIR) spectroscopy, proton nuclear magnetic resonance ( 1 H NMR) spectroscopy and gel permeation chromatography (GPC). The results showed that the molecular weight was significantly reduced as was the glass transition temperature, an indication of chain scission. FTIR showed small changes in chemical structure in the methyl and carbonyl groups after irradiation. Glass transition temperature was significantly different between irradiation at −80 °C and irradiation at 25 °C, however this was a difference of only 1 °C. Ultimately, the results indicate that the sterilization temperature used does not affect PLGA when carried out in a nitrogen atmosphere. Abstract : Highlights: Gamma radiation sterilization of poly(lactide co-glycolide) (PLGA). Effects of low temperature irradiation in an inert atmosphere on the properties of PLGA. Tested with DSC, GPC, tensile testing, NMR and FTIR. Significant differences found in molecular weight before and after irradiation. Further work required to gauge significance of atmosphere on properties.